Patient-Reported Outcomes and Complications Following Breast Reconstruction: A Comparison Between Biological Matrix-Assisted Direct-to-Implant and Latissimus Dorsi Flap - Gao, Peng; Bai, Ping; Kong, Xiangyi; Fang, Yi; Gao, Jidong; Wang, Jing (Frontiers in Oncology, 2022)
Background: Implant-based breast reconstruction has been increasingly becoming the most common method of postmastectomy breast reconstruction in use today. As the traditional autologous reconstruction technique, latissimus dorsi flap (LDF) is employed by surgeons for reconstruction after breast cancer surgery, including partial mastectomy, modified radical mastectomy and others. The authors aim to compare patient-reported outcomes (PROs) and complications between the SIS matrix-assisted direct-to-implant (DTI) breast reconstruction and the autologous latissimus dorsi flap breast reconstruction. Methods: Patients undergoing the SIS matrix-assisted DTI reconstruction or the mastectomy with LDF reconstruction or the partial mastectomy with mini latissimus dorsi flap (MLDF) reconstruction were enrolled in a single institution from August of 2010 to April of 2019. Patients were included for analysis and divided into three groups: those who underwent LDF reconstruction, those who underwent MLDF reconstruction, and patients who underwent SIS matrix-assisted DTI breast reconstruction. Patient-reported outcomes (using the BREAST-Q version 2.0 questionnaire) and complications were evaluated. Results: A total of 135 patients met inclusion criteria: Seventy-nine patients (58.5%) underwent SIS matrix-assisted IBBR, 29 patients (21.5%) underwent LDF breast reconstruction, 27 patients (20%) underwent MLDF breast reconstruction. PROs and complication rates between LDF reconstruction group and MLDF reconstruction group showed no statistically significant differences. Furthermore, BREAST-Q responses found that patients in the whole autologous LDF reconstruction group had better psychosocial well-being, showing a mean score of 84.31 ± 17.28 compared with SIS matrix-assisted DTI reconstruction, with a mean score of 73.52 ± 19.96 (p= 0.005), and expressed higher sexual well-being [ 69.65 ± 24.64 versus 50.95 ± 26.47 (p= 0.016)]. But there were no statistically significant differences between the two groups for postoperative complications. Conclusion: This retrospective study showed no statistically significant differences between LDF breast reconstruction and MLDF breast reconstruction. However, patients in the whole autologous LDF reconstruction group yielded superior patient-reported outcomes than patients in the SIS matrix-assisted DTI reconstruction group in the psychosocial well-being and sexual well-being domains.